Water quality negatively impacts coral occurrence in eutrophic nearshore environments of the Florida Keys - Zoi Thanopoulou; Jacob Patus; Kathleen Sullivan Sealey (Frontiers in Marine Science, 2022)
IntroductionCoral species are negatively impacted by anthropogenic stressors worldwide. Nearshore coastal ecosystems provide an excellent study system for the investigation of the impacts of local land-based stressors such as nutrients on coral assemblages due to their proximity to land based sources of pollution. The nearshore environs of the Florida Keys are an intensively developed and intensively managed system; Florida Keys waters have been characterized by chronic eutrophication since 1999. Benthic communities are known to change or “shift” under chronic eutrophication.ObjectivesThis research examines the patterns of occurrence in stony corals correlating to detailed nearshore water quality measurements. The questions addressed are a) What are the coral assemblages within 500 meters of the shoreline, and which species are resilient to these environs? b) How does water quality impact coral occurrence?MethodsThis study examined the immediate nearshore (0-500m) areas of 13 sites using a randomized blocked experimental design for both water quality and benthic sampling. Water quality parameters measured included chlorophyll-a, nitrates + nitrites (NOx), total nitrogen, total Kjeldahl nitrogen, total phosphorus, Salinity, pH, temperature, and dissolved oxygen. Benthic surveys documented stony coral occurrence using belt transects with point intercept measurements.ResultsStony coral species occurrence was limited at most of the study sites. Siderastrea radians and Porites divaricata were the two common species that appear to have a higher tolerance to eutrophic conditions under these shallow water conditions. Of the 13 study sites, 2 sites had no coral species occurring; this analysis was based on the comparison between sites with and without stony coral species. Water column Chlorophyll-a, pH, dissolved oxygen saturation, temperature, NOx, N:P ratio, total nitrogen and total phosphorus were found to be significantly different between the sites with and without corals. Further multivariate analysis showed a clear clustering of the two groups.ConclusionThe low overall diversity and the higher occurrences of stress tolerant species provide evidence of the effects of coastal eutrophication on the coastal Florida Keys ecosystem. Our data suggest that more conservative water quality thresholds should be posed to improve nearshore biodiversity and ecological functioning of coastal systems.